Individual and Group Performance Evaluation Decission: A Test on An Interaction Between Outcome Information and Group Polarization - Ainun Na’im (The Indonesian Journal of Accounting Research, 2013)
Many decisions are made by groups of individuals such as committees rather than by individuals. In group performance evaluation decisions, two issues can be raised: group polarization and hindsight bias. This experimental study provides a direct test if outcome information interacts with decision levels (individual vs. groups) affecting performance evaluation decisions.This study found that the effect of outcome information is greater in group decisions than those in individual decisions. Regardless of information available ex ante, decision makers are evaluated more favorably by groups than by individuals when the decisions have successful results. On the contrary, when the results are unsuccessful, the decision makers are evaluated more unfavorably by groups than by individuals. Key Words:    Hindsight bias, group decision, group polarization, and performance evaluation.